2018
DOI: 10.1016/j.chest.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Cough Frequency During Treatment Associated With Baseline Cavitary Volume and Proximity to the Airway in Pulmonary TB

Abstract: Cough frequency during treatment is greater and lasts longer in patients with larger cavities, especially those closer to the airway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…More recently a study in Peru found a substantially lower pre-treatment median of 2.3 coughs/hour but replicated the treatment effect on cough frequency with reductions predicting microbiological conversion of sputum [34]. The same group showed a link between greater cough counts as well as persistent coughing on treatment and the presence of larger cavity volumes and proximity of cavities to airways [35]. These findings indicate a correlation between coughing and disease extent but cannot be taken as evidence for cough as a means of transmission.…”
Section: Methodsmentioning
confidence: 99%
“…More recently a study in Peru found a substantially lower pre-treatment median of 2.3 coughs/hour but replicated the treatment effect on cough frequency with reductions predicting microbiological conversion of sputum [34]. The same group showed a link between greater cough counts as well as persistent coughing on treatment and the presence of larger cavity volumes and proximity of cavities to airways [35]. These findings indicate a correlation between coughing and disease extent but cannot be taken as evidence for cough as a means of transmission.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with prior tuberculosis also coughed more. This may be due to more extensive lung damage in these patients [6]. or physiological alterations of the lung that did not fully recover to normality.…”
Section: Plos Onementioning
confidence: 95%
“…Because TOTAL TIME COUGHING was the strongest predictor of TTP, this feature was carried forward to examine determinants of cough severity. Secondarily, because we have previously reported on the association between COUGH EPISODE FREQUENCY and patient characteristics in a separate cohort of HIV-negative Peruvian patients with drug-sensitive tuberculosis [5,6,13], bivariable and multivariable incidence rate ratios comparing COUGH EPISODE FREQUENCY based on clinical characteristics from treatment day 0 to 60 (n = 357) are also reported. TOTAL TIME COUGHING was significantly positively associated with: diabetes (β = 0.86, 95% CI: 0.09, 1.63, p = 0.028); history of prior tuberculosis (β = 1.44, 95% CI: 0.66, 2.22, p<0.001) but not HIV status nor drug resistant tuberculosis.…”
Section: Determinants Of Cough Severitymentioning
confidence: 99%
See 2 more Smart Citations